Approaches to Silence through Scorsese's Silence Film: A Comparison between Western and Eastern Perspectives - Aydemir, Mehmet Ali; Çelik, Kemal (My University, 2023)
Silence, the film, revolves around Christian missionaries who traveled to Japan in the 17th century to propagate Christianity and explores their interactions with the local population. The film portrays silence by strongly associating it with martyrdom and alludes to the suffering of Jesus Christ. This glorification of silence reveals findings related to Western perspectives and an Orientalist attitude. These findings will be analyzed according to Orientalist theory, a theory that investigates Western culture's tendency to exoticize and dominate Eastern cultures, in order to examine how the Western missionaries in the film observed and represented Japanese culture. The analysis will employ content analysis methodology to delve into the themes, symbols, and representations in the film. Additionally, it will draw upon Edward Said's theory of Orientalism and the concept of self-Orientalism. The film identifies instances where the Western representation associates silence with martyrdom and belittles Eastern culture. Examples such as the claim that the Japanese people do not understand Christianity, the depiction of Japan as a barren land, the presentation of Japanese characters as stereotypical figures, and the relegation of Eastern spiritual traditions to a lower status all demonstrate the denigration and marginalization of Eastern culture by the Western perspective. Furthermore, the fact that the film is based on a novel written by a Japanese author necessitates an examination of self-Orientalism.
Keywords: Orientalism; Japan; Christianity; Silence; East-West